AVALIAÇÃO DO IMPACTO DA SAÚDE BUCAL SOBRE A QUALIDADE DE VIDA EM PACIENTES COM DOENÇA PULMONAR OBSTRUTIVA CRÔNICA (DPOC) - Moleta, Jeanny Franciela Kos (2017)
The World Health Organization (WHO) emphasizes that quality of life (QoL) is subjective, multidimensional, and includes both positive and negative aspects. Considering the multidimensional aspects of QoL, we can highlight the influence of oral health in this context, in which research has shown that the oral condition can affect QoL in patients with chronic diseases. The present study aimed to evaluate the impact of oral health on quality of life in patients diagnosed with chronic obstructive pulmonary disease (COPD). Regarding the methodology, the selection of patients was made at the Hospital Universitário Regional de Campos Gerais - HURCG (Ponta Grossa - PR). The study is characterized as a "Cross-Sectional Clinical Study" with two groups (1- Patients with COPD and 2- Control, patients without COPD), with 100 volunteers were defined in each group. The following questionnaires were applied in both groups: OHIP-14 and SF-36. In the form developed for the research were obtained: smoking, demographic data of schooling and dental habits. The socioeconomic condition was evaluated following the Brazilian Economic Classification Criteria of the Brazilian Association of Research Companies. According to the data distribution, the appropriate statistical tests were applied. The significance level was 5%. Regarding the results, we had the participation of 50 women and 50 men in each group, mean age was approximately 62 years (with about 60% of the population over 60 years) and the mean number of teeth was 5,85 teeth. The internal reliability of the questionnaires was evaluated using the alpha Cronbach (α), all α had results higher than 0.74. The COPD group had a greater impact of oral health on QoL in the total sum of OHIP-14 and in the domains: functional limitation, physical pain, psychological discomfort, psychological incapacity and disability. In all SF-36 domains, the COPD group had lower values, indicating a worse overall QoL. In conclusion, patients with COPD have a higher impact on oral health quality of life (HRQoL) compared to a population without COPD, and also have a lower overall QoL.